Informação e Informação Vol. 18, n. 3 (2013) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Informação e Informação Vol. 18, n. 3 (2013)Link de acesso ao númerohttp://www.uel.br/revistas/uel/index.php/informacao/issue/view/899